2010
DOI: 10.1128/iai.00144-10
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Evasion of Phagocytosis Is Mediated by Loss of Swimming Motility and Is Independent of Flagellum Expression

Abstract: Pseudomonas aeruginosa is a pathogenic Gram-negative bacterium that causes severe opportunistic infections in immunocompromised individuals; in particular, severity of infection with P. aeruginosa positively correlates with poor prognosis in cystic fibrosis (CF) patients. Establishment of chronic infection by this pathogen is associated with downregulation of flagellar expression and of other genes that regulate P. aeruginosa motility. The current paradigm is that loss of flagellar expression enables immune ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
151
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 27 publications
5
151
0
2
Order By: Relevance
“…With regard to the contribution of bacterial motility to the recognition and clearance of P. aeruginosa, we recently identified that bacterial flagellar motility is a pattern-recognition signal for phagocytic engulfment by innate immune cells (1,19). Bacteria which have lost flagellar motility, either through loss of the flagellar structural protein FliC or the loss of the stator complexes in the flagellar motor, are ϳ100-fold more resistant to phagocytosis (1,19) by the cells critical for clearance of P. aeruginosa: neutrophils and macrophages (17).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the contribution of bacterial motility to the recognition and clearance of P. aeruginosa, we recently identified that bacterial flagellar motility is a pattern-recognition signal for phagocytic engulfment by innate immune cells (1,19). Bacteria which have lost flagellar motility, either through loss of the flagellar structural protein FliC or the loss of the stator complexes in the flagellar motor, are ϳ100-fold more resistant to phagocytosis (1,19) by the cells critical for clearance of P. aeruginosa: neutrophils and macrophages (17).…”
mentioning
confidence: 99%
“…Bacteria which have lost flagellar motility, either through loss of the flagellar structural protein FliC or the loss of the stator complexes in the flagellar motor, are ϳ100-fold more resistant to phagocytosis (1,19) by the cells critical for clearance of P. aeruginosa: neutrophils and macrophages (17). The P. aeruginosa stators are two partially redundant complexes, MotAB and MotCD, which are not necessary for flagellar assembly, but are required for flagellar rotation and swimming motility (5,33).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to biofilm formation providing resistance to phagocytosis, additional strategies are also used to overcome this host response mechanism. P. aeruginosa can evade phagocytosis by becoming non-motile [37]. Similarly, Staphylococcus aureus forms polysaccharide encased cells under oxygen limited conditions which confer resistance to neutrophil killing [35].…”
Section: Specific Strategies To Evade Host Responsementioning
confidence: 99%